If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + -1) = 12x Reorder the terms: 3(-1 + 5x) = 12x (-1 * 3 + 5x * 3) = 12x (-3 + 15x) = 12x Solving -3 + 15x = 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -3 + 15x + -12x = 12x + -12x Combine like terms: 15x + -12x = 3x -3 + 3x = 12x + -12x Combine like terms: 12x + -12x = 0 -3 + 3x = 0 Add '3' to each side of the equation. -3 + 3 + 3x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = 0 + 3 3x = 0 + 3 Combine like terms: 0 + 3 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| -2x+19=3x+1 | | 2/3(-3)-x=2 | | x+x+x+3x+3x=18 | | 14+21x=14x+35 | | 5(2x+3)=14+4 | | -3-2/3d+1/6d=-4 | | -5x-3=5x-53 | | 8m+2m-6=14+2m | | 6x-9=9x-36 | | -7=-4+a/6 | | 9+x*3=13 | | 3(2+4x)=30 | | (7x-8)(7x-8)=0 | | 6x1/7 | | 2/3(3)-x=2 | | -19=3x-6x+8 | | 18=3x*4 | | 7x+10=5x+20 | | 3+6=3.5m | | 27*n=9 | | 75.00x-250.00=500.00 | | 20x-4x*x-12x=8x*x-23x-3 | | 12+5*x=12 | | x+3x-80=2660 | | 117=13(2x-5) | | 7x+10=5+20 | | 3x-9=7.5+5z | | 14+21x=35+14x | | 2x*3=6 | | -6(-2+x)=24 | | .25z-5=-.2 | | 6p+22=11 |